Autophagy as a Therapeutic Target of Natural Products Enhancing Embryo Implantation - Hyerin Park; Minkyoung Cho; Yoonju Do; Jang-Kyung Park; Sung-Jin Bae; Jongkil Joo; Ki-Tae Ha (MDPI AG, 2021)
Infertility is an emerging health issue worldwide, and female infertility is intimately associated with embryo implantation failure. Embryo implantation is an essential process during the initiation of prenatal development. Recent studies have strongly suggested that autophagy in the endometrium is the most important factor for successful embryo implantation. In addition, several studies have reported the effects of various natural products on infertility improvement via the regulation of embryo implantation, embryo quality, and endometrial receptivity. However, it is unclear whether natural products can improve embryo implantation ability by regulating endometrial autophagy. Therefore, we performed a literature review of studies on endometrial autophagy, embryo implantation, natural products, and female infertility. Based on the information from these studies, this review suggests a new treatment strategy for female infertility by proposing natural products that have been proven to be safe and effective as endometrial autophagy regulators; additionally, we provide a comprehensive understanding of the relationship between the regulation of endometrial autophagy by natural products and female infertility, with an emphasis on embryo implantation.